Relation between the pole and the minimally subtracted mass in dimensional regularization and dimensional reduction to three-loop order - Marquardt, Peter; Mihaila, Luminita (Nuclear physics. B, Particle physics, 2007)
We compute the relation between the pole quark mass and the minimally subtracted quark mass in the framework of QCD applying dimensional reduction as a regularization scheme. Special emphasis is put on the evanescent couplings and the renormalization of the ε-scalar mass. As a by-product we obtain the three-loop on-shell renormalization constants ZmOS and Z2OS in dimensional regularization and thus provide the first independent check of the analytical results computed several years ago.
Gesehen am 12.02.2018